2021
DOI: 10.1371/journal.pone.0246210
|View full text |Cite
|
Sign up to set email alerts
|

Trends and projections of under-5 mortality in Bangladesh including the effects of maternal high-risk fertility behaviours and use of healthcare services

Abstract: Objective This study examines trends and puts forward projections of under-5 mortality (U5M) in Bangladesh and identifies the effects of maternal high-risk fertility behaviours and use of healthcare services. Methods Data from seven waves of the Bangladesh Demographic and Health Survey (1994–2014) were analyzed for trends and projections of U5M and a Chi-square (χ2) test was used to identify if there was any association with maternal high-risk fertility behaviours and use of healthcare services. A multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
7
21
1
1
Order By: Relevance
“…HRFB in mothers also associated with the neonatal mortality; while a study in India identified causal effect of birth spacing on neonatal mortality [14], and also childbearing at teenage was also found to be linked to neonatal mortality [15]. Some previous studies established a relationship between numerous HRFB-related parameters and their detrimental effects on maternal and infant health [7,8,16,17]. Women who start having children at an early age often have more children [18] and this is also associated with adverse maternal, infant and child health outcomes [19].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…HRFB in mothers also associated with the neonatal mortality; while a study in India identified causal effect of birth spacing on neonatal mortality [14], and also childbearing at teenage was also found to be linked to neonatal mortality [15]. Some previous studies established a relationship between numerous HRFB-related parameters and their detrimental effects on maternal and infant health [7,8,16,17]. Women who start having children at an early age often have more children [18] and this is also associated with adverse maternal, infant and child health outcomes [19].…”
Section: Introductionmentioning
confidence: 96%
“…Maternal HRFB is a bio-demographic risk factor that impedes the achievement of lower maternal and child morbidity and mortality [3][4][5][6][7]. Some demographic variables, such as women's age, parity, and birth spacing are the crucial parameters of measuring HRBF including too-early (< 18 years) or too-late (> 34 years) childbearing, short birth intervals (< 24 months) and a higher number of live births (4 or higher) [3,4,7,8]. Although the total fertility rate (TFR) of Bangladesh declined from 3.7 in 1995 to 2.04 in 2020 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh has achieved significant progress in reducing under-five mortality during the Millennium Development Goals period of 2000 to 2015 [13]. However, the rate is still very high at 45 and 30 per 1000 live births for under-five mortality and neonatal mortality, respectively [13, 14]. This presents a challenge in achieving the Sustainable Development Goal 3 (health and wellbeing for all), in particular, its targets to reduce under-five (25 per 1000 live births) and neonatal (12 per 1000 live births) mortality rates by 2030 [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal HRFB is a bio-demographic risk factor that impedes the achievement of lower maternal and child morbidity and mortality [4][5][6][7][8]. Some demographic variables, such as women's age, parity, and birth spacing are the crucial parameters of measuring HRBF including too-early (<18 years) or too-late (>34 years) childbearing, short birth intervals (<24 months) and a higher number of live births (4 or higher) [4,5,[8][9][10]. Although the total fertility rate (TFR) of Bangladesh declined from 3.7 in 1995 to 2.04 in 2020 [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies identi ed the linkage between various factors of HRFB and its adverse impacts on the mother and child health [8,10,18,19]; however, there is a dearth of literature that assessed the risk factors of HRFB in Bangladesh using the latest round BDHS dataset. Therefore, the present study was undertaken to identify the determinants associated with high-risk fertility behaviour of reproductive aged women (15-49 years) in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%